Finite‐time stabilization for a class of more general p‐normal nonlinear systems with input and output nonlinearities - Zhang, Jiao‐Jun; Song, Zhibao; Li, Ying (International journal of robust and nonlinear control, 2024)
This study investigates the global finite‐time state feedback stabilization for a class of more general p‐normal nonlinear systems subjects to input time‐delay and uncertain output function under rational powers. A novel control input compensation signal comprising a finite integral of previous control values is presented, and an equivalent system with control input dependent‐free time delay is obtained by introducing a variable transformation technique that includes the compensation signal. A suitable controller is designed in line with the homogeneous domination method to ensure the globally finite‐time stability of the closed‐loop system. Finally, the effectiveness of the proposed control scheme is verified through a numerical simulation and an induction heater circuit system.